Brain cyst as an unusual delayed complication of temporal lobectomy in drug-resistant epilepsy: a case report. - Barreto-Acevedo, Elliot (2021)
Anterior temporal lobectomy is a technique that has proven, with a very high level of evidence (60-73% of the cases), to reach a seizure-free status in patients with drug-resistant focal temporal lobe epilepsy. It is a technique that although generally safe, cannot be considered entirely free of complications. Superior homonymus quadrantanopsia and depression have been reported, for instance, as the most frequent  complications. While the occurrence of a late-onset symptomatic brain cyst, is very rare. The case of a patient who was subjected to right temporal lobectomy and presented this unusual complication is described here, with inclusion of a review of pertinent literature and proposed pathophysiological mechanisms.